Pets : An Anthology - Castro, Jordan (Napoli : Tyrant Books, 2019)
Akutagawa, Ryunosuke ; Beattie, Ann ; Bird, Reagan ; Butler, Blake ; Choi, Ryan C. K. ; Clune, Michael W. ; Cottrell, Patty Yumi ; DeWitt, Annie ; Hodson, Chealsea ; Igarashi, Yuka ; Iskandrian, Kristen ; Leidner, Mark ; Lin, Tao ; McClanahan, Scott ; Manguso, Sarah ; Nutt, David ; Okoyomon, Precious ; Pink, Sam ; Polek, Nicolette ; Scanlan, Kathryn ; Schutt, Christine ; Whitten, Mallory
boek